Vibrio harveyi infections induce production of proinflammatory cytokines in murine peritoneal macrophages via activation of p38 MAPK and NF-κB pathways, but reversed by PI3K/AKT pathways. (February 2022) - Yu, Guili; Yu, Hong; Yang, Qiankun; Wang, Jinxin; Fan, Hui; Liu, Gang; Wang, Lei; Bello, Babatunde Kazeem; Zhao, Panpan; Zhang, Honggang; Dong, Jingquan
Abstract: Vibrio harveyi is a zoonotic pathogen that can infect humans through wounds and cause severe inflammatory responses. Previous studies have reported that the Toll like receptors (TLR) mediated MAPK, AKT and NF-κB signaling pathways are involved in innate immune system resistance to pathogen invasion. However, the molecular mechanism of these pathways, as well as their involvement in V. harveyi infection remains elusive. This study established a V. harveyi infection model using murine peritoneal macrophages (PMs). Various techniques, including western blotting, ELISA, RT-qPCR, immunofluorescence, inhibition assays, were used to explore the roles of TLRs, MAPK, AKT and NF-κB signaling pathways in V. harveyi -induced inflammatory responses. ELISA assays showed that V. harveyi infection triggered proinflammatory cytokines secretion in PMs. RT-qPCR and inhibition assays showed that TLR2 participated in V. harveyi infection and up-regulated the proinflammatory cytokines secretion in murine PMs. Western blotting data showed that the phosphorylation of p38, JNK, AKT, and NF-κB p65 were significantly increased partly mediated by TLR2. In addition, immunofluorescence assays revealed that the NF-κB p65 translocated into nucleus in response to V. harveyi infection. The secretion of IL-1β, IL-6, IL-12, and TNF-α were considerably reduced when the p38 MAPK and NF-κB signaling pathways were blocked, whereas blocking of AKT significantly increased the expression of IL-1β, IL-6, IL-12, and TNF-α. These findings indicate that V. harveyi infection induces inflammatory responses in murine PMs via activation of p38 MAPK and NF-κB pathways, which are partly mediated by TLR2, but are inhibited by PI3K/AKT pathways. Highlights: V. harveyi induces inflammatory responses in murine PMs. The MAPK, AKT and NF-κB pathways were activated against V. harveyi infection in PMs . V. harveyi induce inflammation in PMs via p38 MAPK and NF-κB pathways. Activation of AKT pathway relieve V. harveyi induced inflammatory responses in PMs.